Analysis of Human, Technical, and Environmental Factors: A Case Study of Fatal Incident Triggers Among Workers at PT Freeport Indonesia - Navisya Delia; Ahmad Mustofa (LPPM Sekolah Tinggi Ilmu Ekonomi Ganesha, 2026)
This study offers an original contribution by integrating a systematic perspective to identify multidimensional causes of fatal work accidents in the mining sector, particularly at PT. Freeport Indonesia. The objective of this research is to analyze the underlying factors contributing to fatal accidents by examining human, technical, and environmental dimensions. The study employs a Systematic Literature Review (SLR) method, synthesizing recent and relevant scholarly sources to provide a comprehensive understanding of accident causation. The empirical findings reveal that fatal incidents are not caused by a single factor but rather by an interaction of safety procedure violations by workers (human factors), failures in ventilation systems and the absence of adequate gas detection tools (technical factors), as well as hazardous geological conditions that facilitate the accumulation of toxic gases (environmental factors). These findings highlight the complexity of occupational safety risks in mining operations. The implications of this study emphasize the need for integrated safety management, including enhanced worker training, technological system improvements, proactive environmental risk mitigation, and the strengthening of organizational safety culture to prevent future accidents.